AMBIGUIDADE COMO INVENTIVIDADE: UM ESTUDO SOBRE O SINCRETISMO RELIGIOSO NA FRONTEIRA ENTRE A ANTROPOLOGIA E A TEOLOGIA - Reis, Gustavo Soldati (2010)
This thesis is a study regarding the problem of religious syncretism, when it is considered in the dialogue between anthropology and theology. For this purpose, the study employs a hermeneutical exercise of conceptual resignification, based upon various theories about syncretism and their anthropological and theological uses, seeking support in the thought of Michel de Certeau and Paul Tillich for that resignification. Thus, the perspective of Certeau regarding a heterological reflection of culture and the notion of demonic in theology and philosophy of meaning of Tillich provide the basis for the perception of syncretism as a theory of mediation between religion and culture. This means that syncretism operates in a dialectical relation with its named pole, in this thesis, of diacretism , considering the cultural and religious dynamic as an inventive space, a position that manifests ambiguous aspects of the creation of positive meanings (experience of syncretistic approximation) and the creation of distorted meanings (experience of diacretistic fragmentation), the essence of the relation with the sacred, lived culturally. The culture, understood as space for the living of the religious, expresses itself in a profound relation between tactics and strategies, denoting the ambiguity previously affirmed, when it recognizes that the social actors in interaction, even when marked by proper places strategically established, as places of power, do not inhibit the formation of tactical actions that inventively subvert these same places, offering the rightful cultural dynamic. The thesis analyses, also, as a case study, the implications of this comprehension of syncretism for the interpretation of the religious experience of the Guarani and Kaiowá native indigenous groups, on the indigenous land of Dourados, MS, on the frontier between tradition and translation performed by the indigenous people, based on the Presbyterian Indigenous Church Project (IIP), resignifying its alternative religiosity in the interface with the multiple Christianities present in the villages, affirming the possibility of a religious teko retã ( a way of being that is plural, multiple ), based on the syncretistic and diacretistic relations that are proposed.